2001
DOI: 10.1177/153537020122600905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Minerals on Leptin Secretion in Streptozotocin-lnduced Hyperglycemic Mice

Abstract: The effects of lithium, magnesium, vanadate, and zinc on leptinemia and leptin secretion by adipose tissue were investigated in streptozotocln-(STZ) induced hyperglycemic mice. After the administration of studied minerals in drinking water for 4 weeks, fasting serum leptin concentrations were elevated, accompanied by normoglycemia in STZ-injected mice, regardless which minerai was provided (P < 0.05). However, the in vitro administration of lithium, magnesium, and vanadate did not significantly influence the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
3
1
4
Order By: Relevance
“…Currently, studies show that leptin may enhance or diminish bone architecture, and its affects may be mediated both through a central mechanism as well as a peripheral pathway [20]. Leptin concentrations were significantly lower in diabetic mice compared to controls, consistent with previous studies in STZ-induced diabetic rodents [21]. However, IGF-I therapy failed to alter leptin levels in diabetic mice, suggesting that while leptin deficiency might contribute to skeletal deficits observed in diabetic mice, improvements in bone microarchitecture, bone formation and strength achieved with IGF-I therapy cannot be attributed to changes in leptin.…”
Section: 4 Discussionsupporting
confidence: 81%
“…Currently, studies show that leptin may enhance or diminish bone architecture, and its affects may be mediated both through a central mechanism as well as a peripheral pathway [20]. Leptin concentrations were significantly lower in diabetic mice compared to controls, consistent with previous studies in STZ-induced diabetic rodents [21]. However, IGF-I therapy failed to alter leptin levels in diabetic mice, suggesting that while leptin deficiency might contribute to skeletal deficits observed in diabetic mice, improvements in bone microarchitecture, bone formation and strength achieved with IGF-I therapy cannot be attributed to changes in leptin.…”
Section: 4 Discussionsupporting
confidence: 81%
“…[33] This is an interesting result as leptin and leptin receptors are structurally similar to IL-6. [33] In conclusion, it was demonstrated that metabolic defects that arise in mice with hyperglycemia induced by STZ could be restored by supplementation of zinc in physiological doses. Maybe the most important study about the relationship between zinc and leptin is the one by Ott and Shay.…”
Section: Leptin and Zinc Relation In Food Intakementioning
confidence: 94%
“…It was reported that zinc deficiency inhibited leptin secretion from the fatty tissue, whereas supplementation of a physiological dose of zinc increased both leptin levels and glucose intake in mice with hyperglycemia induced by streptozotocin (STZ). [33]…”
Section: Leptin and Zinc Relation In Food Intakementioning
confidence: 99%
“…Chen et al, [16][17] observed increased leptin at low zinc levels and further zinc supplementation to the experimental animals in the same study stimulated further increase in leptin levels. This implies that zinc may either directly affect leptin gene expression or indirectly cause leptin production.…”
Section: Discussionmentioning
confidence: 62%